The impact of solid cooking fuels on the health of rural South African households - Tatham, Julia (School of Economics, 2022)
Indoor Air Pollution (IAP) from the combustion of solid cooking fuels has been proven to adversely affect the health of household residents. Those most affected by IAP are the poorest and most vulnerable members of society, specifically poor women and children residing in rural households. This study evaluates the impact of using solid cooking fuels on various health outcomes of residents in rural South Africa, using the nationally representative General Household Survey 2018. Propensity Score Matching Methods are used to address the confounding of variables associated with the use of solid cooking fuels and health outcomes. We find that the use of solid fuels significantly increases the risk of suffering from Acute Respiratory Illnesses (ARI's) as well as increasing the risk of residents reporting a poor health status. Our analysis goes on to evaluate separate gender and age groups and find some evidence that women and the elderly may suffer relatively more adverse health outcomes from the use of solid cooking fuels. Our results suggest that IAP from the combustion of solid fuels poses a threat to health of South Africans residing in rural households. Hence policy should focus on providing access to clean sources of energy for cooking in rural areas.